Laser induced resistivity of chiral single wall carbon nanotubes. (10th July 2020) - Twum, Anthony; Mensah, Samuel Yeboah; Edziah, Raymond; Arthur, Augustine
Abstract: Using the Boltzmann transport equation within the semi-classical approximation with constant relaxation time, we theoretically studied the dynamics of electrons in chiral single wall nanotubes (SWNTs) subjected to a temperature gradient (∇T) in the presence of a combined direct current and high frequency alternating fields. We obtained an expression for the resistivity ( ρ c ) of the SWNTs which varies with temperature and depends among others on material's chiral angle ( θ h ), dc field strength (Eo ) and ac field amplitude (Es ). Our results show that chiral SWNTs exhibit metallic behavior with resistivity increasing approximately linearly with temperature over a wide temperature range well above 100 K. Based on the low chiral resistivity obtained for the SWNTs at room temperatures, we propose these materials as good candidates for possible optoelectronic applications.